Fabrication of uniform Ru-doped NiFe2O4 nanosheets as an efficient hydrogen evolution electrocatalyst. Issue 97 (20th November 2019) - Niu, Siqi; Li, Siwei; Hu, Jing; Li, Yuzhi; Du, Yunchen; Han, Xijiang; Xu, Ping
Abstract : Ru-doped NiFe2 O4 nanosheets exhibit outstanding electrocatalytic hydrogen evolution activity and stability. Abstract : Here we demonstrate the synthesis of uniform Ru-doped NiFe2 O4 nanosheets with robust hydrogen evolution reaction (HER) activity in alkaline solution, with an extremely low overpotential of 18 mV versus a reversible hydrogen electrode (RHE) at a current density of 10 mA cm −2 and a Tafel slope of 27 mV dec −1 .